β2 Integrins As Regulators of Dendritic Cell, Monocyte, and Macrophage Function - Schittenhelm, Leonie; Hilkens, Catharien M.; Morrison, Vicky L. (Frontiers in Immunology, 2017)
Emerging evidence suggests that the β₂ integrin family of adhesion molecules have an important role in suppressing immune activation and inflammation. β₂ integrins are important adhesion and signalling molecules that are exclusively expressed on leukocytes. The four β₂ integrins (CD11a, CD11b, CD11c and CD11d paired with the β2 chain CD18) play important roles in regulating three key aspects of immune cell function: recruitment to sites of inflammation; cell-cell contact formation; and downstream effects on cellular signalling. Through these three processes, β2 integrins both contribute to and regulate immune responses. This review explores the pro- and anti-inflammatory effects of β₂ integrins in monocytes, macrophages and dendritic cells (DC), and how they influence the outcome of immune responses. We furthermore discuss how imbalances in β₂ integrin function can have far-reaching effects on mounting appropriate immune responses, potentially influencing the development and progression of autoimmune and inflammatory diseases. Therapeutic targeting of β₂ integrins, therefore, holds enormous potential in exploring treatment options for a variety of inflammatory conditions.